Retrospective analysis of the analgosedative efficacy and safety of midazolam combined with fentanyl in mechanically ventilated neonates - Lin, Fangfang; Lin, Shuidi; Cai, Wenhong; Ren, Yanli (Frontiers in Pediatrics, 2025)
PurposeTo compare the analgosedative efficacy and safety of the combination of midazolam and fentanyl with those of midazolam monotherapy in mechanically ventilated neonates.Materials and methodsWe conducted a single-center retrospective analysis of mechanically ventilated patients in our neonatal intensive care unit from April 1, 2021 to December 1, 2024. After dividing patients into midazolam + fentanyl (M + F) and midazolam (M) groups according to their respective sedation/analgesia regimens, we conducted intergroup comparisons of pain scores, ventilator parameters, and vital signs 5 min pre-treatment and at post-treatment time points (1 h, 3 h, 12 h, 24 h, 48 h). We also compared pre-and post-treatment (3 h, 24 h, 48 h) non-invasive hemodynamic parameters; adverse reactions; and discharge outcomes of the two groups.ResultsA total of 210 neonates were included, with 106 in the M + F group and 104 in the M group. N-PASS pain scores obtained 5 min pre-treatment were similar between the two groups (P > 0.05); however, N-PASS scores were significantly lower in the M + F than in the M group at each post-treatment time point (1 h, 3 h, 12 h, 24 h, 48 h) (all P < 0.05). Ventilator parameters (MAP, FIO2) obtained 5 min pre-treatment were similar (P > 0.05), but were significantly lower at each post-treatment time point (1 h, 3 h, 12 h, 24 h, 48 h) in the M + F group (all P < 0.05). Pre- and post-treatment (1 h, 3 h, 12 h, 24 h, 48 h) vital signs did not differ between the two groups (P > 0.05). Pre-and post-treatment (3 h, 24 h, 48 h) non-invasive hemodynamic parameters were similar between the two groups (P > 0.05). There were no significant intergroup differences in adverse reactions or discharge outcomes (P > 0. 05).ConclusionThe combination of midazolam and fentanyl relieved pain and reduced ventilator parameters more effectively than midazolam monotherapy, without increasing adverse reactions or worsening discharge outcomes among mechanically ventilated neonates.